2021
DOI: 10.1177/11297298211015035
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peripheral venous catheter failure: A prospective cohort study of 5345 patients

Abstract: Purpose: The objective of this study was to determine the independent risk factors associated with peripheral venous catheter (PVC) failure and develop a model that can predict PVC failure. Methods: This prospective, multicenter cohort study was carried out in nine tertiary hospitals in Suzhou, China between December 2017 and February 2018. Adult patients undergoing first-time insertion of a PVC were observed from catheter insertion to removal. Logistic regression was used to identify the independent risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
13
2
2
Order By: Relevance
“…However, the most common factors that increased the incidence of phlebitis were drugs, such as nicardipine, noradrenaline, amiodarone, and levetiracetam. Some findings of this study pertaining to critically ill patients were similar to the findings of studies in a general hospital ward setting [10][11][12][19][20][21][22][23][24][25][26][27][28][29][30]. Previous studies related to general wards showed the increased risk of phlebitis with the administration of nicardipine and noradrenaline [12,[31][32][33].…”
Section: Discussionsupporting
confidence: 83%
“…However, the most common factors that increased the incidence of phlebitis were drugs, such as nicardipine, noradrenaline, amiodarone, and levetiracetam. Some findings of this study pertaining to critically ill patients were similar to the findings of studies in a general hospital ward setting [10][11][12][19][20][21][22][23][24][25][26][27][28][29][30]. Previous studies related to general wards showed the increased risk of phlebitis with the administration of nicardipine and noradrenaline [12,[31][32][33].…”
Section: Discussionsupporting
confidence: 83%
“…A total of 24 studies (encompassing 16562 PVCs) were included (Arias‐Fernández et al, 2017; Carr et al, 2018; Cicolini et al, 2009; Cicolini et al, 2014; Furtado and d. R. 2011; Lee et al 2019; Lee et al 2009; Marsh et al, 2018; Simin et al, 2019; Singh, Bhandary, & Pun, 2008; Urbanetto et al, 2017; Uslusoy, & Mete, 2008; Wei et al, 2019; Zhu, Wang, & Wen, 2016; do Rego Furtado L.C. 2011; Erdogan, & Denat, 2016; Kaur et al, 2011; Saini et al, 2011; Chen et al, 2021; Fernández‐García, Mata‐Peón, & Avanzas‐Fernández, 2017; Göransson, & Johansson, 2012; Liu et al, 2020; Loureiro et al 2016; Lulie et al, 2021). The pooled results showed that the heterogeneity among the studies was high ( I 2 = 60%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies (encompassing 16562 PVCs) were included (Arias-Fernández et al, 2017;Carr et al, 2018;Cicolini et al, 2009;Cicolini et al, 2014;Furtado and Erdogan, & Denat, 2016;Kaur et al, 2011;Saini et al, 2011;Chen et al, 2021;Fernández-García, Mata-Peón, & Avanzas-Fernández, 2017;Göransson, & Johansson, 2012;Liu et al, 2020;Loureiro et al 2016;Lulie et al, 2021). The pooled results showed that the heterogeneity among the studies was high (I 2 = 60%).…”
Section: The Comparison Of the Incidence Of Total Complications Betwe...mentioning
confidence: 99%
“…Local adverse reactions originating from several factors may alter, eventually or circumstantially, a person's venous network, their health conditions and clinical management of puncture sites where intravascular catheters (IVC) are used in the infusions [3][4][5][6][7][8] . Therefore, these are events that influence people's health care and experiences.…”
Section: Introductionmentioning
confidence: 99%